Pengaruh Inovasi Produk dan Orientasi Kewirausahaan Terhadap Kinerja Pemasaran (Studi Pada Industri Mikro Kecil Makanan di Kota Denpasar) - IA Cynthia Saisaria Mandasari (Warmadewa Management and Business Journal (WMBJ), 2020)
The number of Micro Small Industries in Denpasar City has now increased. This causes increasingly fierce competition in the food industry sector in Denpasar City. Facing intense competition, entrepreneurs are required to always innovate in their products and support the entrepreneurial character in order to improve their marketing performance. The purpose of this research is to study conversation motivation and innovation towards marketing products. This research was conducted in the city of Denpasar on the owners or managers of the food micro-small industry. The number of samples taken was 100 food business owners, using a non probability sampling method, specifically purposive sampling. Data collection was carried out through a questionnaire. The analysis technique used is path analysis. Based on the results of the analysis of this study it was found that the variables that encourage entrepreneurship fully positively influence marketing performance. Improving communication skills can be done so it can improve marketing performance. Official partial product innovation has a significant positive effect on marketing performance. The more often entrepreneurs do product promotion, the more they will increase. Variables talk about entrepreneurship and innovation that are supported simultaneously and significantly to marketing performance. This shows that the better it is to increase entrepreneurship and to increasingly improve products that will increase the level of marketing in a company.